Heart Failure in Family Medicine - Siniša Franjić (International Journal of Global Health, 2020)
Heart failure is a serious condition in which the amount of blood squeezed out of the heart every minute is insufficient to meet the body’s normal needs for oxygen and nutrients. Although some people wrongly believe that the term heart failure means that the heart has stopped, we must say that the term heart failure actually means that the heart has weakened and lost its ability to work. Heart failure has many causes including a many of diseases. Heart failure occurs most often in older people because they are much more likely to suffer from diseases that cause heart failure. Although heart failure gets worse over time, people with the condition can live for years.
Keywords: Heart Failure